Prevención de Caídas: Seguridad en el Hogar - Leigh Ann Martin (EDIS)
Revised! FCS2229-Span, a 1-page inventory by Leigh Ann Martin, is a Spanish Language version of "Fall Prevention: Home Safety Inventory." It can be used to find areas in the home which can increase the risk of dangerous falls as people age, and to improve safety in those areas. Published as part of the Elder Nutrition and Food Safety (ENAFS) program by the UF Department of Family Youth and Community Sciences, May 2006.